High-resolution seismic exploration - Li, Qing-Zhong (Society of Exploration Geophysicists, 2017)
Capitalizing on knowledge learned over decades and combining underlying theory with practical cases, this book presents a systematic analysis of the issues involved in high-resolution seismic exploration. Translated from the original Chinese edition published in 1993 by Petroleum Industry Press and now updated to reflect contemporary developments, the book is adept at clarifying the objectives and approaches toward better precision in seismic prospecting. It provides innovative views on fundamental concepts including: perspective resolution and perspective S/N; the empirical relationship between compressional velocity (Vp) and absorption coefficient (Q); constructing basin absorption models; understanding sand layer tracking; improving dynamic and static corrections of near-surface effects as well as deconvolution; achieving maximum effective bandwidth of seismic data; and regressive seismic impedance inversion. It is an excellent reference for those involved in seismic prospecting research, data processing, and geologic interpretation, and it is recommended for geoscientists and engineers as well as professors and graduate students.-- Source other than Library of Congress.
"In 1993, the Petroleum Industry Press (PIP) published The way to obtain a better resolution in seismic prospecting: a systematical analysis of high resolution seismic exploration in Chinese. PIP holds the worldwide copyright of the original work, which is still available from PIP. With permission from PIP, the Society of Exploration Geophysicists (SEG) has translated the original work into English under the title High-resolution seismic exploration"--Title page verso.
Keywords: Seismic prospecting.; elektronické knihy; electronic books